Identification Of Potential Ergonomic Hazards In The Upper Body Using SNI 9011: 2021 At PT. X - Rosmala Asty Novita Putri; Usi Lanita; David Kusmawan; Willia Novita Eka Rini; Budi Aswin (Sekolah Tinggi Ilmu Kesehatan Kesdam IV, Diponegoro Semarang, Indonesia, 2024)
In a rapidly evolving industry, the focus on the risk of Repetitive Occupational Muscle Disorder (GOTRAK) is increasing. Compliance with Indonesian National Standard (SNI) 9011:2021 on ergonomics in the workplace is essential to identify and control these risks. This study aims to pinpoint ergonomic hazards at PT X associated with GOTRAK, so as to provide important insights to improve worker welfare. The study, conducted using a quantitative approach, involved workers from wet and dry production processes in manufacturing. Primary data collection from 57 rotating shift workers, who each worked for 8 hours each day, showed that 32 respondents (56%) faced high upper body GOTRAK risk with the right shoulder (26.3%), left shoulder (14%), and lower back (12.3%) being the most vulnerable areas. The evaluation showed significant ergonomic risks in wet production work such as pre-breaking, breaking, pressing, and handling rubber blankets, and in dry production work such as transporting blankets, grinding, drying, transferring cakes from trolleys, pressing, and weighing. These conditions are considered hazardous, requiring immediate action to improve working conditions and worker welfare.